The impact of magnetic fields on the chemical evolution of the supernova-driven ISM - Pardi, Anabele-Linda; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract: We present three-dimensional magneto-hydrodynamical simulations of the self-gravitating interstellar medium (ISM) in a periodic (256 pc)3 box with a mean number density of 0.5 cm−3. At a fixed supernova rate we investigate the multi-phase ISM structure, H2 molecule formation and density-magnetic field scaling for varying initial magnetic field strengths (0, 6 × 10−3, 0.3, 3 μG). All magnetic runs saturate at mass-weighted field strengths of ∼1-3 μG but the ISM structure is notably different. With increasing initial field strengths (from 6 × 10−3 to 3 μG) the simulations develop an ISM with a more homogeneous density and temperature structure, with increasing mass (from 5 to 85 per cent) and volume filling fractions (VFFs; from 4 to 85 per cent) of warm (300 < T < 8000 K) gas, with decreasing VFFs from ∼35 to ∼12 per cent of hot gas (T > 105 K) and with a decreasing H2 mass fraction (from 70 to < 1 per cent). Meanwhile, the mass fraction of gas in which the magnetic pressure dominates over the thermal pressure increases by a factor of 10, from 0.07 for an initial field of 6 × 10−3 μG to 0.7 for a 3 μG initial field. In all but the simulations with the highest initial field strength self-gravity promotes the formation of dense gas and H2, but does not change any other trends. We conclude that magnetic fields have a significant impact on the multi-phase, chemical and thermal structure of the ISM and discuss potential implications and limitations of the model.